Theories of development and economic development in Nigeria - Olalere, Fasilat Abimbola (Technium Social Sciences Journal, 2021)
Various scholars have developed various theory on what development entails and how it may be attained. Despite the disparity of viewpoints in these theories, the common ground amongst the various schools of thought is that, development leads to improvement of human lives. Hence, the concern of most government of the world is to create policies that would enable development, particularly from the economic perspective, given the perception of economy as the sub-structure of the society. Over the years, Nigerian government has devised various approach to attain economic development in Nigeria. This paper set out to put these various attempts into perspective. It sought to demonstrate why these methods have been non-yielding in the attainment of the developmental objectives of the country. One of the factors identified as being responsible for the developmental woes of the country is Nigeria’s lack of consistency and wanton changes in its national development plans with each successive government at various times. The paper concludes that for Nigeria to attain real development, it must not continually depend solely on the crude oil revenue but move away from its mono-cultural economy by developing other sector of the economy, especially agricultural and manufacturing sector.